Immune response against gastrointestinal nematodes and the potential application of immortalized cell lines in the sheep industry - Vu, Sang Van; Niciura, Simone Cristina Meo; Gondro, Cedric (Vietnam Journal of Science and Technology, 2024)
The world’s sheep industry faces significant health challenges due to endoparasite infections. One effective management approach to control these parasites is through the activation of the host’s immune system. Vaccination emerges as a potential method to control gastrointestinal nematode (GIN) parasites while addressing the need for animal food products devoid of harmful chemicals. However, the development of an efficient anti-parasite vaccine requires a comprehensive understanding of the immune responses elicited by the sheep to control GIN infection. Mast cells, recognized as tissue-resident immune cells primarily involved in IgE-mediated immune responses, play a pivotal role in both innate and adaptive immunity. Based on their location and function, mast cells are classified into tissue and mucosal mast cells and play an important role in defending the host against specific pathogens. Mucosal mast cells, located in the body’s mucosal surfaces, are capable of initiating early immune responses against bacterial and viral infection, thereby contributing to effective immunity in animals. Advancing our knowledge about mast cell biology through the successful culturing of mast cell lines holds great promise for the sheep industry. It may lead to the development of targeted vaccines that can further improve the productivity, welfare, and economic sustainability of the sheep industry. In this paper, we review the effective immune responses employed by sheep to combat GIN infections and highlight the crucial roles of mast cells in establishing host immune responses to eliminate GIN.